2017
DOI: 10.1590/0034-737x201764010010
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento, produtividade e qualidade de fibra de algodão colorido influenciados pela população de plantas

Abstract: Submetido em 11/02/2014 e aprovado em 16/12/2016. 1 Parte do trabalho de conclusão de curso da segunda autora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
3
0
5
Order By: Relevance
“…However, Kaggwa-Asiimwe et al (2013) stated that in populations with over 100,000 plants ha -1 , fiber yields were found to reduce. Alves et al (2017) studied populations with densities between 25,000 and 125,000 plants ha -1 and found that a reduction in productivity was present with densities greater than 70,000 plants ha -1 . In the present study, when significant, the effect of the plant population on fiber yield was positive with densities up to 100,000 plants ha -1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Kaggwa-Asiimwe et al (2013) stated that in populations with over 100,000 plants ha -1 , fiber yields were found to reduce. Alves et al (2017) studied populations with densities between 25,000 and 125,000 plants ha -1 and found that a reduction in productivity was present with densities greater than 70,000 plants ha -1 . In the present study, when significant, the effect of the plant population on fiber yield was positive with densities up to 100,000 plants ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained in the present study agree with those of Meredith Junior et al (2012) who evaluated the effect of genotype (G), environment (E), and the G x A interaction and concluded that STR is primarily influenced by G. In other words, STR is a characteristic that is highly influenced by the cultivar and hardly influenced by the environment. According to Alves et al (2017), fiber strength is a characteristic that is not influenced by the plant population. According to Lima and Bélot (2020), fiber was found to vary from medium to resistant values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, reduz a aplicação de fertilizantes e o custo com mão de obra sem diminuir a produtividade (Zhi et al, 2016). Alves et al (2017) destacam a importância da realização de pesquisas que visem alcançar uma grande produtividade e adequado crescimento de novas cultivares de algodão.…”
Section: Introductionunclassified
“…Basicamente, o arranjo de plantas dependerá da população final (nº de plantas x unidade de área), da densidade (número de plantas por metro) e do espaçamento entre fileiras. Avaliando o efeito da população de plantas no crescimento, produtividade e qualidade de fibra,Alves et al (2017) observaram que a maior produtividade foi obtida em populações de até 73 mil plantas ha -1 , em contrapartida, populações de até 125 mil plantas ha -1 apresentaram melhores características relacionadas a qualidade de fibra (resistência à ruptura e índice de fiabilidade). Por outro lado, em condições de segunda safra, o aumento da densidade de plantas, a utilização do espaçamento adensado de 45 cm entre fileiras, não ocasionou aumento na produtividade e qualidade de fibra, conforme observado por Ferreira et al(2015).…”
unclassified